2013
DOI: 10.1016/j.burns.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Photographic assessment of burn wounds: A simple strategy in a resource-poor setting

Abstract: Burn assessment with digital photography is a valid and affordable alternative to direct clinical exam, alleviating access issues to burn care in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
3
35
3
Order By: Relevance
“…It has already been documented that burn size can be assessed using photographs on patients with light-skin types [17,23] and there were indications that this applied even to those with dark-skin types [20]. We confirmed that burn size can be appropriately diagnosed on dark-skin types and even more so by specialised physicians familiar with cases of that type.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…It has already been documented that burn size can be assessed using photographs on patients with light-skin types [17,23] and there were indications that this applied even to those with dark-skin types [20]. We confirmed that burn size can be appropriately diagnosed on dark-skin types and even more so by specialised physicians familiar with cases of that type.…”
Section: Discussionsupporting
confidence: 78%
“…In the literature at hand, image-based diagnosis was compared to the bedside diagnosis made by the same assessor [16,[19][20][21]23]. In the current study the diagnosis was determined at bedside by a burn surgeon in service when the patient was treated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations